An analysis of equity markets cointegration in the european sovereign debt crisis - Ferreira, N. B.; Oliveira, M. M. (Open Journal of Finance, 2014)
A simpli?ed presentation of an empirical ?nding in the portfolio diversi?cation literature is that diversifying across countries is more effective in reducing risks than diversifying across industries. While the linear approach is not designed to capture a signi?cant integration, this is not the case when Gregory and Hansen cointegration tests are used to assess this relation by allowing for instability in these long-run relations. The present work investigates the existence of long-run relations between the Portuguese and other markets under stress. Interestingly, the only market that did not follow this trend was Spain. In overall, our results found six cointegration vectors: two within the group of European emerging markets (Portugal, Italy and Ireland) and the other four between the Portuguese market and the mature markets (France, United Kingdom, Germany and United States).